Transitioning from physical to virtual classrooms during the pandemic: impact on learning motivation of postgraduate students / Jasmine Jain - Jain, Jasmine (UiTM Press, 2021)
Learning is a behavior influenced by many factors. Students’ learning motivation is the core of making learning process efficient and learning results effective. However, learners’ learning motivation is constantly changing and is influenced by various intrinsic and extrinsic factors, especially during the changing environments of learning during the Covid-19 pandemic. This research aims to study the postgraduate student’s experience on their transition from physical to virtual classrooms from the aspect of learning motivation. This phenomenological research utilised a purposive sampling and involved five participants from People’s Republic of China, who are studying in a Master coursework programme in a private university in Malaysia. Participants were interviewed and data collected were analysed for content. The findings indicated that the experience of learning has changed, but motivation remained high due to better intensity of content understanding. The feedback given by lecturers were timely and instantaneous, on par with their experience during physical classes, which was not a cause for concern. However, the two dimensions such as heightened distractions and lacked peer interaction were claimed to be the factors causing lower motivation.